Efficacy and safety of flexibly dosed paliperidone palmitate in Chinese patients with acute schizophrenia: an open-label, single-arm, prospective, interventional study - Si TM (Dove Medical Press, 2015)
Tianmei Si,1 Kerang Zhang,2 Jisheng Tang,3 Maosheng Fang,4 Keqing Li,5 Jianmin Zhuo,6 Yu Feng6 1Peking University Institute of Mental Health, Key Laboratory of Mental Health, Ministry of Health, Beijing, People’s Republic of China; 2Shanxi Medical University First Hospital, Shanxi, People’s Republic of China; 3Mental Health Center of Shandong Province, Shandong, People’s Republic of China; 4Mental Health Center, Tongji Medical College, Huazhong University of Science and Technology, Hubei, People’s Republic of China; 5Mental Health Center of Hebei Province, Hebei, People’s Republic of China; 6Janssen Research and Development, Beijing, People’s Republic of China Abstract: This open-label, single-arm, multicenter, 13-week, prospective study explored the efficacy, safety, and tolerability of paliperidone palmitate (150 milligram equivalents [mg eq] [day 1], 100 mg eq [day 8], both deltoid injections; 75–150 mg eq, deltoid/gluteal injection) in Chinese patients with acute schizophrenia (Positive and Negative Syndrome Scale [PANSS] total score ≥70), who previously had unsatisfactory therapeutic effect following oral antipsychotic treatment (without washout period). Primary efficacy endpoint was percentage of patients with ≥30% improvement in the PANSS total score at the end of 13 weeks. Secondary efficacy endpoints included change from baseline to end of week 13 in PANSS total score, PANSS subscale scores, Marder factor scores, Clinical Global Impressions–Severity score, and Personal and Social Performance Scale scores. Overall, 477/610 enrolled patients (full analysis set, 78.2%) completed the study (men: 55.1%; women: 44.9%; mean age: 31.5 years). Total, 443/610 (72.6%, full analysis set) patients achieved primary endpoint (mean [standard deviation] change from baseline: –30.9 [19.51]). All secondary endpoints demonstrated significant improvement at the end of 13 weeks. One death occurred during this acute phase. The most common (>5%) treatment-emergent adverse events were extrapyramidal disorders (8.4%). The efficacy and safety data are consistent with other short-term, placebo-controlled studies of paliperidone palmitate conducted in similar populations. Keywords: antipsychotic, long-acting injectable, PANSS